PSYCHIATRIC PROBLEMS IN AN AFGHAN VILLAGE - Mufti, Khalid A; Naeem, Farooq; Ayub, Mohammad; Saifi, Farida; Haroon, Asad; Dagarwal, Saif-ur- Rehman; Kingdon, David (Journal of Ayub Medical College Abbottabad, 2005)
Background: The rates of psychiatric disorders might be very high in Afghanistan. The country has faced many years of war and violence and therefore this is hardly surprising. We are describing the results of a community survey conducted by clinicians in a small village of Eastern Afghanistan. This study was carried out to measure prevalence of psychiatric disorders among the people living in a small village in the Nangerhar, Afghanistan. We also wanted to measure the associated demographic variables. Methods: A structured interview schedule, Mini International neuropsychiatry Interview Schedule (MINI), was used to measure psychiatric morbidity. Results: More than 70% of the population fulfilled criteria for some form of mental illness. Conclusions: The rates of mental health problems are very high in Afghanistan. Any efforts to rebuild this war torn country should take sufficient measures in building mental health services with special emphasis on mental health problems. Keywords: Violence, Trauma, Psychiatric disorders, war